Pengembangan Potensi Wisata Pantai Desa Bugel, Kabupaten Kulon Progo - Visnhu, Bartolomeus Galih (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Bugel village, located at Kulon Progo district, at the most west part of Yogyakarta province. This particular village is filled with natural resources. From very fertile soil, beaches and ocean, and farm land. The agricultural and industrial sector within this village is very well developed. But, it's such a shame that their tourism sector and beach is left behind by a lot. For that reason, it is crucial that the villagers gets the push and education needed for them to start being initiative at how to improve these 2 sectors. All data used within the composing and activity of this program is obtained through secondary data. Based on the data, several education programs have been constructed as the “push” the villagers needed to initiate in improving their tourism sector which will most probably start at their charming beach, and some education for how to market their new ideas.